Rodent models of obsessive compulsive disorder: Evaluating validity to interpret emerging neurobiology. (14th March 2017) - Zike, Isaac; Xu, Tim; Hong, Natalie; Veenstra-VanderWeele, Jeremy
Highlights: Genetic and environmental risk factors for obsessive compulsive disorder (OCD) have been difficult to identify. Neuroimaging studies implicate cortico-striatal-thalamo-cortical circuitry in OCD. Chronic administration of a serotonin reuptake inhibitor is the only effective medication treatment in OCD. Rodent models have been proposed based upon genetic, pharmacological, immune, and circuit approaches. No single model fully captures the human disorder, but multiple models converge on abnormal cortico-striatal signaling. Abstract: Obsessive Compulsive Disorder (OCD) is a common neuropsychiatric disorder with unknown molecular underpinnings. Identification of genetic and non-genetic risk factors has largely been elusive, primarily because of a lack of power. In contrast, neuroimaging has consistently implicated the cortico-striatal-thalamo-cortical circuits in OCD. Pharmacological treatment studies also show specificity, with consistent response of OCD symptoms to chronic treatment with serotonin reuptake inhibitors; although most patients are left with residual impairment. In theory, animal models could provide a bridge from the neuroimaging and pharmacology data to an understanding of pathophysiology at the cellular and molecular level. Several mouse models have been proposed using genetic, immunological, pharmacological, and optogenetic tools. These experimental model systems allow testing of hypotheses about the origins of compulsive behavior. Several models have generated behavior that appears compulsive-like, particularly excessive grooming, and some have demonstrated response to chronic serotonin reuptake inhibitors, establishing both face validity and predictive validity. Construct validity is more difficult to establish in the context of a limited understanding of OCD risk factors. Our current models may help us to dissect the circuits and molecular pathways that can elicit OCD-relevant behavior in rodents. We can hope that this growing understanding, coupled with developing technology, will prepare us when robust OCD risk factors are better understood.